The Effect of Using Edpuzzles in Teaching Vocabulary - Rini, Erica Setiyo; Marpaung, Marlin Steffi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This study investigates the effectiveness of using the Edpuzzle application in improving students’ vocabulary knowledge and understanding in English language learning. An experimental design was employed with pre- and post-tests conducted on seventh-grade students from SMP 1 Parongpong, Jawa Barat. The experimental group utilized Edpuzzle, while the control group employed conventional teaching methods. Data were analyzed using descriptive statistics, normality tests, and paired sample t-tests. The results indicate a significant improvement in vocabulary knowledge among students who utilized Edpuzzle. The post-test scores (M=68.92) were substantially higher than the pre-test scores (M=41.97), demonstrating the effectiveness of Edpuzzle in enhancing students’ vocabulary skills. However, challenges such as limited access to technology and unstable network connectivity were identified as factors influencing the extent of vocabulary improvement. In conclusion, integrating Edpuzzle into language teaching practices holds promise for enhancing vocabulary learning outcomes and engaging students in active learning experiences.